Plágio, pirataria, fair use e a (des)criminalização da violação de direito autoral - Smith, Virgínia Luna (2012)
The aim of this doctoral thesis is to instigate the debate on the criminalization of the most usual forms of copyright violation, considering the standoff between the defenders of a stricter legislation to fight piracy and plagiarism and the liberals who believe in the legitimate use of intellectual creations. The impacts of technological improvements on the market, society, communication and on the body of laws will be examined using the Tridimensional Theory of Law, developed by Miguel Reale, to assess to which extent the current facts that would consist in violation of intellectual property are mutually entangled with the penal norms that impose sanctions against violating behaviors and the values present in a society that is becoming more global, connected and computerized every day